Tadabbur Surat Al-Insyirah untuk Menurunkan Stres Akademik Mahasiswa - Eko Hardi Ansyah; Hindun Muassamah; Cholichul Hadi (Jurnal Psikologi Islam dan Budaya, 2019)
The purpose of this research is to examine the effect of Al-Insyirah contemplation to reduce the academic stress level on Islamic university students. Al-Insyirah contemplation is an Islamic term that related to deep contemplation and visualization for the psychological aspects of the surah of Al-Insyirah. This research used the pre-post experimental design. The participants were 16 students who experience academic stress. Before the subjects were trained by Al-Insyirah contemplation, academic stress scale was administered to measure the academic stress level. Then Al-Insyirah contemplation were trained to them, which consists of six steps. After two weeks, the academic stress scale was measured again. The result of before and after the contemplation were analysed using t-test analysis. The results show that Al-Insyirah contemplation could lower the students' academic stress. Consequently, students after using this contemplation are able to think positively to solve various challenges and difficulties in campus life.